Legal Standing and Liability of Grabfood Drivers Vis-À-Vis Consumers within Grabfood Services - Indra Aditama I. Dunggio; Syamsuddin Baco; Marini Citra Dewi (Rechtsvinding, 2026)
This study aims to determine the legal status of GrabFood drivers in the legal relationship between the application provider company, consumers, and business actors, as well as to analyze the legal responsibilities of GrabFood drivers towards consumers in the provision of GrabFood services. The research method used is normative legal research. The results of the study indicate that the legal status of GrabFood drivers in the provision of GrabFood services is as a working partner of the application provider company whose task is to carry out order delivery services from business actors to consumers. The legal relationship between drivers and the company is based on a partnership agreement, while the relationship between consumers and the application provider arises from an electronic agreement made through the GrabFood application. In carrying out the service, drivers have an obligation to carry out delivery tasks in accordance with operational standards set by the company and maintain the security and condition of orders until they are received by consumers. This study also shows that the legal responsibility of GrabFood drivers towards consumers can arise if the driver commits negligence or errors that result in losses for consumers, such as delivering the wrong order, losing the order, damaging food during the delivery process, or taking actions that are contrary to the terms of service.